Implementation of Early Childhood Literacy Through Word Picture Games at Fastabiqul Khairat Kindergarten, Bima City - R.P.M. Ganif Abimanyu; Hendra; Masita (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The purpose of this study was to examine how early childhood literacy is used in word play activities at Fastabiqul Khairat Kindergarten, Bima City. This study employed a qualitative, descriptive methodology. The tools used included observation guidelines, interview guidelines, and documentation guidelines. Data collection techniques were conducted through observation and interviews with teachers, as well as documentation studies involving children and teachers as research subjects. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The research results show that word play activities under pictures improve children's literacy skills, particularly in enhancing their comprehension, improving their understanding of language, and fostering their confidence in communication. Furthermore, the use of visual media in literacy activities can also increase children's interest in learning and engage them actively in the learning process. This study found that picture-based word play is a great way to help young children learn basic literacy in a fun and sustainable way.